“Stability of the public finance sector” in the COVID-19 pandemic - Wojciech Bożek (Prawo Budżetowe Państwa i Samorządu)
The state of public finances in Poland during the COVID-19 pandemic has been changing dynamically. An analysis of statistical data on public debt (and its components), as well as data related to unmatured obligations, allows to indicate possible areas of a threat to the stability and security of the public finance sector. For the purpose of this research two research methods have been mainly used, i.e. the dogmatic and legal method and the analytical method. The Author's intended to emphasize the importance of axiological foundations of the public finance law in a process of establishing and applying this law. He also wanted to present the applicable financial and legal solutions to control a state of public debt in Poland. Author analysed current law, data on the amount of the state public debt, the debt of the State Treasury, as well as unmatured obligations of the State Treasury and public finance sector entities (under sureties and guarantees granted in 2016-2020). Due to the perceived differences, it was also considered necessary to discuss a methodology of calculating public debt in Polish and EU law. This is because in this regard significant changes can be seen, especially during the COVID-19 pandemic.